2004
DOI: 10.1029/2003jd003735
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of lightning and the possible initiation/triggering of lightning discharges by the lower positive charge center in an isolated thundercloud in the tropics

Abstract: [1] The evolution of lightning and the shape of recovery curves after multiple-discharge flashes in a thundercloud have been studied from the surface measurements of electric field and Maxwell current near a tropical thundercloud. Observations suggest a tripole structure of the cloud and that its lower positive charge center (LPCC) plays a dominant role in initiating/triggering an intracloud (IC) or cloud-to-ground (CG) lightning discharge. IC discharges in the initial stage of thundercloud are followed by CG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 45 publications
(59 reference statements)
4
38
0
Order By: Relevance
“…8b and d) and the negative CG lightning initiation point height is between 4 -6 km. -CG flashes begin between the main negative charge and lower positive charge, which is consistent with previous observations (Williams 1989;Pawar and Kamra 2004;Qie et al 2005;Nag and Rakov 2009). However, Case 4 shows a stronger net positive charge region than Case 2, contributing to the initiation of more -CG flashes.…”
Section: Charge Structure and Lightning Dischargessupporting
confidence: 81%
“…8b and d) and the negative CG lightning initiation point height is between 4 -6 km. -CG flashes begin between the main negative charge and lower positive charge, which is consistent with previous observations (Williams 1989;Pawar and Kamra 2004;Qie et al 2005;Nag and Rakov 2009). However, Case 4 shows a stronger net positive charge region than Case 2, contributing to the initiation of more -CG flashes.…”
Section: Charge Structure and Lightning Dischargessupporting
confidence: 81%
“…It is worthy to note that both these electric field changes are of equal magnitude. Pawar and Kamra (2004) have already reported such two-polarity electric field changes, one followed immediately by another. They have attributed this to two different lightning discharges of opposite polarity.…”
Section: Meteorological Observationmentioning
confidence: 91%
“…Electrical structure of the thunderstorm Previous studies have revealed that in thunderstorms with non-inverted polarity charge structures (with midlevel negative and upper level positive charge regions), most of the electric field changes produced by lightning are of negative polarity, indicating removal of negative charge from overhead (Jacobson and Krider 1976;Livingston and Krider 1978;Mohanty and Pradeep Kumar 2004;Pawar and Kamra 2004 (Figures 4 and 5). Although it is difficult to distinguish the CG from the IC discharges based only on singlepoint observations of the electric field and Maxwell current data, most of the visually confirmed CG discharges were found to be transporting positive charge to the ground on May 11.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the median negative peak current in severe storms was very low (i.e., as low as 12 to 16 kA) and was noticeably less than in nonsevere storms (i.e., by at least 10%). Although earlier reports suggest most thunderstorms with inverted polarity charge structures were characterized by a high degree of severity, Qie et al (2005) and Kamra (2004 and2009) have also reported some non-severe thunderstorms over the Tibetan Plateau and India, with a wide spread and strong positive charge in the lower portion of cloud. Majority of lightning activity arises from lower negative dipole of these thunderclouds.…”
Section: Introductionmentioning
confidence: 95%